The Use of RAP (Read, Ask, Put) to Improve Reading Comprehension : A Systematic Review - Novasyari, Ressy (Global Expert: Jurnal Bahasa dan Sastra, 2025)
This article aims to conduct a systematic review of using RAP (Read, Ask, Put) to improve reading comprehension. The search strategy is based on the following keywords: "RAP (Read, Ask, Put) strategy", "Reading Comprehension" from Google Scholar. Based on the results of this article, only 6 articles were analyzed. One of the strategies to improve reading comprehension is Read, Ask, Put (RAP) because this strategy can make the students improve their reading comprehension, memory of important information, and also enlarge their vocabulary. RAP (Read, Ask, Put) is a strategy that can improve the reading comprehension of students with and without disabilities and is extremely flexible. It can be used for elementary, middle, and high school students across many different content areas. This strategy can help the students improve their understanding of the text that is better than when they only read. The strategy needs students to be involved in reading materials through questioning and paraphrasing to enlarge their comprehension of the material. From the questioning and paraphrasing, students process information for a better understanding of what they read. Keywords: RAP (Read, Ask, Put) strategy, Reading Comprehension